Mutsaers en andere dieren Naar een diergerichte benadering in de Nederlandse letterkunde - Fraipont, Barbara (Lage Landen Studies, 2023)
Mutsaers en andere dieren is a literary study on the issue of animals in the creative oeuvre by Dutch writer and artist Charlotte Mutsaers. How is an animal perspective portrayed in Mutsaers's art? What cultural meanings can be attributed to the animals in the artist's work? In this book, Barbara Fraipont explores these questions based on perspectives from animal philosophy and methodological perspectives drawn from animal studies. In doing so, she offers an in-depth and innovative reading of human-animal configurations in Mutsaers's visual and narrative work.